Myeloid Leukosis (J-virus) - An International Broiler Industry Concern - Gary D. Butcher; Richard D. Miles (EDIS)
Myeloid leukosis (ML) or myelocytomatosis/myeloblastosis is caused by a retrovirus in the Avian Leukosis/Sarcoma Group of Retroviruses (ALV). This ALV subgroup J virus (ALV-J), which is identified as the etiologic agent for ML, has caused substantial losses in heavy breeders in many areas of the world. This document is VM131, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.